The international law of belligerent occupation / Yoram Dinstein. - Dinstein, Yoram (Cambridge University Press, 2019)
Belligerent occupations existed in both World Wars and have occurred more recently in all parts of the world (including Iraq, Afghanistan, the former Yugoslavia, Congo, Northern Cyprus, Nagorno-Karabakh, Georgia, Eritrea and Ethiopia). Owing to its special length - exceeding half a century and still in progress - and the unprecedented flow of judicial decisions, a special focus is called for as regards to the occupation of Palestinian territories by Israel. International law addresses the subject of belligerent occupation in some detail. This second, revised edition updates the text (originally published in 2009) in terms of both State practice and doctrinal discourse. The emphasis is put on decisions of the Security Council; legislation adopted by the Coalition Provisional Authority in Iraq; and predominantly case law: international (Judgments of the International Court of Justice, the International Criminal Tribunal for the Former Yugoslavia and the European Court of Human Rights; Advisory Opinions and Arbitral Awards) as well as domestic courts.